Assessment of walkability along Katipunan Avenue - Cortez, Elaine Hazel D.; Razon, Josephine Vivian DV.; Regidor, Jose Regin F. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
This paper assesses the walkability conditions along Katipunan Avenue through the use of mobile applications Walkability and SafetiPin. It aims to determine the overall rating and per parameter rating from each of the applications and to provide necessary recommendations to improve walkability from ratings acquired. Since traffic congestion is observable along the avenue during peak hours, the improvement of its walking facilities will encourage more pedestrians to switch to walking for short distance travel to alleviate traffic congestion. Additionally, provisions of pathways and necessary facilities will provide security and improve safety of the pedestrians. Both applications have nine parameters that were evaluated by a group of crowd-sourced surveyors who are frequent users of the avenue. The group, which was composed of students and workers divided into the male and female genders, evaluated 14 segments for the southbound side and 13 segments for the northbound side. The division was based on the avenue's compliance with the National Building Code standards. The results concluded that Katipunan Avenue has poor walking conditions as the ratings of its northbound and southbound sides failed to attain passing standards of both applications. For Walkability application, no segment passed and the lowest scoring parameters were disability infrastructure, amenities, and quality of crossing points. For SafetiPin application, only six segments have passed and the lowest scoring parameters were security, light, and visibility. Moreover, it was observed the most of the segments do not comply with the National Building Code standards particularly for railings, structures designed for persons with disabilities and parking. Only the standards for overhangs and headroom were significantly followed. The provisions and recommendations made for the improvement of facilities are included at the end of the paper.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Walking -- Quezon City, Philippines